Research in the history of economic thought and methodology. Vol. 29, pt.1 - Biddle, Jeff.; Emmett, Ross B. (Bingley, U.K. : Emerald, 2011)
The collection includes both refereed articles and review essays. The articles highlight research on the role of western economic advisors in China before the Communist Revolution (Paul Trescott), John Ryan on minimum wage legislation, a symposium on Clement Juglar, and a comparison of recent work in the history of economics and the history of science. Review essays on new publications examine a range of subjects, including: David Humes political economy,; conceptions of economic morality in American thought; Frank Knight and the Austrians on institutions; Friedrich Engels; Austrian views on entrepreneurship; Coase and Pigou on government intervention; Hayek and conservatism; the history of the'living wage' notion; methodological consideration of economics and econometrics; and Paul Heynes essays on economic and ethics.
Building and defining behavioral economics / Floris Heukelom -- The Poor Laws in 19th century England : historiography of the debate on the controversial link between social justice and economic advantage / Alain Clent -- Frank Knight, John Dewey, and American pragmatism : a further note / Luca Fiorito -- A.D. Roy : the forgotten father of portfolio theory / Edward J. Sullivan -- Gerhard Colm on John Maurice Clark's economics of planning public works / Luca Fiorito, Matias Vernengo -- The scope of analysis in the socialist calculation debate / D.W. MacKenzie -- Studying economic institutions : an exercise in existential choice : a tribute to Alan Schmid and appraisal of alternative economic structures / Charles J. Whalen -- Life of Smith Ross' / Willie Henderson -- and Shionoya / Renee Prendergast -- Capitalism and the JewsMuller's / Jonathan S. Feinstein -- Reviving the invisible HandLal's / Willie Henderson.
Mode of access: World Wide Web.
Keywords: Economics -- History